Altered Mitochondrial Dynamics Contributes to Propofol-induced Cell Death in Human Stem Cell–derived Neurons. (November 2015) - Twaroski, Danielle M.; Yan, Yasheng; Zaja, Ivan; Clark, Eric; Bosnjak, Zeljko J.; Bai, Xiaowen
Abstract : Background: Studies in developing animals have shown that anesthetic agents can lead to neuronal cell death and learning disabilities when administered early in life. Development of human embryonic stem cell–derived neurons has provided a valuable tool for understanding the effects of anesthetics on developing human neurons. Unbalanced mitochondrial fusion and fission lead to various pathological conditions including neurodegeneration. The aim of this study was to dissect the role of mitochondrial dynamics in propofol-induced neurotoxicity. Methods: Terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate in situ nick-end labeling staining was used to assess cell death in human embryonic stem cell–derived neurons. Mitochondrial fission was assessed using TOM20 staining and electron microscopy. Expression of mitochondrial fission-related proteins was assessed by Western blot, and confocal microscopy was used to assess opening time of the mitochondrial permeability transition pore (mPTP). Results: Exposure to 6 h of 20 μg/ml propofol increased cell death from 3.18 ± 0.17% in the control-treated group to 9.6 ± 0.95% and led to detrimental increases in mitochondrial fission (n = 5 coverslips per group) accompanied by increased expression of activated dynamin-related protein 1 and cyclin-dependent kinase 1, key proteins responsible for mitochondrial fission. Propofol exposure also induced earlier opening of the mPTP from 118.9 ± 3.1 s in the control-treated group to 73.3 ± 1.6 s. Pretreatment of the cells with mdivi-1, a mitochondrial fission blocker rescued the propofol-induced toxicity, mitochondrial fission, and mPTP opening time (n = 75 cells per group). Inhibiting cyclin-dependent kinase 1 attenuated the increase in cell death and fission and the increase in expression of activated dynamin-related protein 1. Conclusion: These data demonstrate for the first time that propofol-induced neurotoxicity occurs through a mitochondrial fission/mPTP-mediated pathway. Abstract : In supratherapeutic doses, propofol increased mitochondrial fission; key proteins involved in fission were increased. Suppression of these proteins mitigated the increases in mitochondrial fission and reduced toxicity. Propofol accelerated mitochondrial permeability transition pore (mPTP) opening; blockade of fission rescued the mPTP opening time. The data indicate that propofol, when administered in supratherapeutic concentrations, may induce neurotoxicity via a mitochondria fission and mPTP pathway.